Latihan Fisik : Gait Training Exercise Terhadap Penurunan Risiko Jatuh pada Lansia dengan Penyakit Tidak Menular - Maula, Anita Nikmal (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2024)
Introduction: Falls are a physical problem that often occurs in the elderly, with increasing age physical, mental and bodily function conditions decline. Preventing the risk of falls can be done through gait training exercises. Objective: To determine the effect of gait training exercise on reducing the risk of falls in elderly people with non-communicable diseases. Method: This research design used Quasy Experimental pre & post tests in the intervention group. The number of samples in this study was 58 respondents with the sampling technique used was simple random sampling. This research was carried out in Plombokan Village on March 27-April 15 2023. The measuring tool used in this research used the time up and go test (TUGT). Results: There was a significant effect between before and after being given gait training exercise on reducing the risk of falls in the elderly with a p value = 0.001 (p ? 0.05). This research suggests that physical exercise, gait training exercise, can reduce the risk of falls in the elderly.